Application Database of Comprehensive Emergency Neonatal and Obstetric Service in Sampang Hospita - Yenik Dyah Andarini; Arief Hargono (Jurnal Berkala Epidemiologi, 2015)
Comprehensive Emergency Obstetric and Neonatal Care (CEmONC) are maternal and neonatal essential or emergency care that aimed at saving mothers and newborns. CEmONC activities at the Hospital involve several service units so a database is needed to integrate data and information according to needs. This study aims to develop a CEmONC database model at the Regional Public Hospital of Sampang District (RSUD Kabupaten Sampang). This research was conducted through a qualitative approach with the type of research is action research in the form of developing a database model. The scope of CEmONC database development includes maternal and neonatal services. The development of the CEmONC database model uses a systems approach that is input, process, and output. The subjects in this study were Hospital Management, CEmONC Team, and Recording and Reporting Officers of RSUD Kabupaten Sampang. Analysis of the recording and reporting system of RSUD Kabupaten Sampang found several problems, which are the non-uniform register format, duplication of records, data storage that is still manual, processing reports that have not been automated and the resulting information is still limited. The results of this study are the CEmONC database prototype based on the information needs of maternal and neonatal services. The developed CEmONC database can produce the information needed by the CEmONC team so that it can be utilized for monitoring and evaluating CEmONC performance at the Hospital. Implementation of the use of the CEmONC database needs to be supported by the availability of facilities and infrastructure, qualified human resources, maintenance management systems, and training to improve the ability of CEmONC reporting officers.